Bilateral Progressive Idiopathic Annular Lipid Keratopathy - Ramon C. Ghanem; Vinícius C. Ghanem; Gustavo Victor; Milton Ruiz Alves (Case Reports in Ophthalmological Medicine)
Purpose. To report two unusual cases of idiopathic lipid keratopathy with symmetrical bilateral annular corneal lipid infiltration and describe confocal microscopy findings. Methods. Case reports. Results. We report two patients with bilateral peripheral deep stromal lipid deposits beginning in an arcuate pattern and progressing to a complete annular shape. Cholesterol crystals were observed in the paracentral area in both cases with characteristic crystalline-like structures in the confocal microscopy. Deep thin corneal blood vessels were observed in one patient, but no cause for then was established, despite decades of followup. This patient had an idiopathic limbitis as well, occurring in episodes. No previous ocular trauma, systemic disease or family history was reported for both cases. Conclusion. These two cases of idiopathic annular lipid keratopathy were observed for more than a decade with documented slow and insidious progression of the infiltrates, in spite of the use of topical steroids in one case. In the majority of other reported cases, a penetrating keratoplasty was made necessary. Differently, we showed that the visual acuity can remain quite good for years with very slow deterioration.